Exploring the unconventional: health professionals’ experiences into medication-free treatment for patients with severe mental illness - Elisabeth C. Klæbo Reitan; Henriette Riley; Tordis Sørensen Høifødt; Valentina C. Iversen; Anne Høye (BMC Psychiatry)
Abstract Background In January 2017, the Norwegian government mandated the establishment of an inpatient unit for “medication-free treatment” for patients with severe mental illness at the University Hospital of North Norway in Tromsø. This study aims to explore the employees’ experiences with this unit. Method Focus group interviews were conducted October 2021 – February 2022. For analysis, the participants were divided into three groups; S (staff working at the medication-free unit), M (people involved in management at the unit) and T (therapists working elsewhere in the hospital). The analysis followed the Systematic Text Condensation and interviews were recorded, transcribed and analysed using NVivo software. Results Health professionals described their experiences with medication-free treatment through five main concepts: 1) Employees’ motivation; 2) Frames; 3) Network; 4) Relations; and 5) Patients’ motivation. Staff and management expressed strong motivation for an alternative to “treatment as usual,” focusing more on recovery and relationships than on the absence of medication. Therapists from other hospital areas highlighted resource allocation concerns and expressed a desire to learn from the unit. Challenges were acknowledged by all groups. Conclusion The term “medication-free treatment’’ might be misleadning. While patiens at the unit can use medications, there is a strong emphasis on patient autonomy and the option to taper off medication and live a life without them. The study adds valuable knowledge about the the experiences of employees working at a medication-free unit, and provides insights into the complexity of treating severe mental illness, both with and without medication. It highlights the importance of sufficient time, stability and resources to focus on each patient’s strengths and challenges. All employees agree that tailored measures in long-term treatment and a clear focus on recovery should be integral, even without an emphasis on “medication-free treatment”.